Dynamics and Control of a Vibrating System with Hyperchaotic Behavior Using an Electronic Circuit Implementation - Daum, Hilson H. [UNESP]; Tusset, Angelo M.; Ribeiro, Mauricio A.; Balthazar, Jose M. [UNESP]; Bueno, Atila M. [UNESP]; Litak, Grzegorz (Springer Nature, 2022)
In this paper, an electronic circuit based on Macek equations was developed in which the phenomenon of hyperchaos was observed. Synchronization of signals was applied using the technique optimal linear feedback control (OLFC) and embedded in digital signal processor (DSP), with the circuit with hyperchaotic behavior as a master system and a periodic slave system embedded in the DSP along with the applied control technique. Within the context presented, it was possible to carry out the synchronization in phase between the systems, i.e., taking the system with periodic behavior to hyperchaos.
Keywords: DSP; Nonlinear dynamics; OLFC control; Synchronization